Tanggung Jawab Notaris Dalam Penerbitan Akta Perjanjian (Studi Putusan PN Pontianak No. 60/Pdt.G/2023/PN.Ptk) - Alindri, Amalia Sekar; Kurniawan, Bramastha Farel Ikmal; Budisulistyani, Nabila Inayati; Hastuti, Wasti (Universitas Muara Bungo, 2025)
This study explores the responsibilities of notaries in issuing deeds of agreement with a focus on Case No. 60/Pdt.G/2023/PN.Ptk at the Pontianak District Court. Law as a part that integrates various aspects of society plays an important role in maintaining balance and justice. Notaries, as an honorable legal profession, have a great responsibility to ensure compliance with legal norms and professional codes of ethics. The case that occurred involved a dispute over a deed of cooperation agreement for the construction of a housing unit issued by a Notary, and allegations of default against one of the parties to the agreement. This study aims to understand and provide recommendations regarding the responsibilities of notaries in the context of law and codes of ethics. The research method used in this study is juridical-normative with an analytical prescriptive approach, using secondary data from literature studies. The results of the analysis show that the responsibilities of notaries cover civil and administrative aspects. The role of a notary must be carried out with integrity, impartially, and in accordance with legal provisions and codes of ethics. This study also found that the lack of socialization regarding the notary code of ethics can hinder the enforcement of professional responsibility.